The THE CORRELATION OFBODY MASSINDEX AND POST-RESUSCITATION ALBUMIN LEVELS WITHTHE MORTALITY OF BURNPATIENTS AT PROFNGOERAH GENERAL HOSPITAL PERIOD 2020-2022 - Andiswari, Kadek Yurika; Samsarga, Gede Wara; Hamid, Agus Roy Rusly Hariantana; Sanjaya, I Gst. Putu Hendra (E-Jurnal Medika Udayana; Vol 13 No 2 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i02.P09, 2024)
Background: Burn injuries are associated with high mortality and morbidity. The incidence of death resulting from burns can be influenced by various prognostic factors, with nutritional status being a significant contributor. Therefore, assessing nutritional status through the calculation of body mass index (BMI) and post-resuscitation albumin levels becomes imperative. Purpose: This study aims to explore the correlation between BMI and post-resuscitation albumin levels with the mortality of burn patients at Prof Ngoerah General Hospital during the period 2020-2022. Methods: This research adopts an observational analytical approach, utilizing a cross-sectional research design and consecutive sampling techniques. The study relies on secondary data, specifically medical records of burn patients. Out of a total of 134 medical records, 100 were selected based on adherence to inclusion and exclusion criteria. Results: The study reveals median values for age (42.5), BMI of 23.9 and albumin levels 24 hours post resuscitation recorded at 2.235. The Spearman test analysis conducted on 100 samples reveals a notable correlation between these variables and the mortality of burn patients (r = 0.263; PR 1.707; 95% CI 1.163 – 2.504; p = 0.008). The chi-square test analysis regarding the association between post-resuscitation albumin levels and burn patient mortality also demonstrates a significant relationship (PR 2.390; 95% CI 1.358 – 4.207; p = 0.000). Conclusion:  In conclusion, there is a statistically significant association between mortality and both BMI and post-resuscitation albumin levels among burn patients treated at the Prof Ngoerah General Hospital during the period 2020-2022. Keywords: Post resuscitation albumin, mortality, BMI, burns